Correlations between fresh properties of self-consolidating concrete including palm oil fuel ash - Safiuddin, M.; Salam, M.A.; Jumaat, Mohd Zamin (2011)
Palm oil fuel ash (POFA) has been used successfully as a supplementary cementing material in various types of concrete. In the present study, self-consolidating concrete (SCC) was produced by using POFA as a partial replacement of ordinary portland cement (OPC). In total, sixteen SCC mixes were prepared by varying water to binder (W/B) ratio, POFA content, and high-range water reducer (HRWR). POFA was used by replacing 0-30 of OPC by weight at the W/B ratios ranging from 0.25 to 0.40. The filling ability, passing ability and segregation resistance of various SCC mixes were investigated. The filling ability was determined with respect to slump flow, 50-cm slump flow time, inverted slump cone flow spread and time, and V-funnel flow time. The passing ability was examined with respect to J-ring flow. In addition, the segregation resistance was assessed with regard to sieve segregation index and column segregation factor. Based on the data obtained, the correlations for the fresh properties of SCC were sought. The experimental findings showed strong correlations between most of the fresh properties of SCC.